2002
DOI: 10.1111/j.1746-1561.2002.tb07339.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Theater Production About Eating Behavior of Children

Abstract: This study evaluated "All's Well That Eats Well," a theater production performed in 20 schools in the Twin Cities, Minn., metropolitan area in winter 2000. The production sought to change food-related knowledge and food choices concerning fruits and vegetables among children in grades 1-6. The study used a pretest-posttest design with two randomly-assigned, sequential intervention-control groups (N = 4,093). All students completed surveys prior to and then following the theater production and the classroom and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…It has been suggested that drama may be a cost-effective way for health care organisations to promote health among young people in the community (Perry et al 2002). An attempt was made to alter the HIV knowledge, attitudes and risk behaviour of young people in socially deprived areas of Glasgow through the use of drama (Elliot et al 1996).…”
Section: Theatre In Health Care Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that drama may be a cost-effective way for health care organisations to promote health among young people in the community (Perry et al 2002). An attempt was made to alter the HIV knowledge, attitudes and risk behaviour of young people in socially deprived areas of Glasgow through the use of drama (Elliot et al 1996).…”
Section: Theatre In Health Care Educationmentioning
confidence: 99%
“…Drama, or theatre, has been used as an educational medium to promote healthy lifestyles (Cheney et al 2006;Elliot et al 1996;Perry et al 2002); teach communication skills to trainee health professionals (Case and Brauner 2010;Baldwin 2009;Kumagai et al 2007;Rosenbaum et al 2005;Deloney and Graham 2003;Shapiro and Hunt 2003); promote environmental awareness (Gaskell and Taylor 2002); encourage the general public to engage in health policy development (Nisker et al 2006) and to disseminate the results of research studies (Gray et al 2000). Drama has been used with a range of audiences, including adults, young people, children, and rural communities.…”
Section: Theatre As Educationmentioning
confidence: 99%
See 3 more Smart Citations